Growth and Proline Accumulation in Response to Osmotic Stress Induced by Polyethylene Glycol Treatment in Tacca le-ontopetaloides Cultured In Vitro - Martin, A. F.; Hapsari, B. W.; Rudiyanto; Ermayanti, T. M. (International Journal of Agricultural Technology, 2018)
Tacca leontopetaloides known as Polynesian arrowroot is a wild tuberous perennial herb. In addition, T. leontopetaloides is a valuable plant not only as staple food but also as a medicinal herb. Nonetheless, there are very few literatures and research on the potential of this plant. In this study, the effect of polyethylene glycol (PEG) as stress osmoticum in T. leontopetaloides cultured in vitro on growth and proline accumulation was investigated. The shoot culture of T. leontopetaloides was subjected to six levels of PEG concentrations (2.5; 5; 7.5; 10; 12.5 and 15%). Growth parameter was evaluated by observing shoot height, number of shoots, number of leaves and number of roots for 6 weeks of culture. After 6 weeks of culture, fresh weight and proline content were determined. The results showed that number of shoots and number of leaves increased after 2.5% PEG treatment while number of roots increased after 5% PEG treatment. Conversely, higher concentrations of PEG inhibited growth. In line with this, culture fresh weight decreased along with the increase of PEG concentrations. To summarize, the growth of culture decreased along with the increase of PEG concentrations. In contrast, proline concentration increased along with the increase of PEG concentrations.